The Effect of Social Support on Person-Environment Fit and Employees' Affective Commitment - Lidia; Adi Rahmat; Fahmi Oemar (SAINS ORGANISASI, 2022)
This study aims to determine the effect of social support on person-environment fit and employee affective commitment. The population of this research is ASN employees who are registered in the government service of Indragiri Hilir Regency. Sampling using total sampling with a total sample of 142. The analytical technique used in this study is PLS Structural Equation Modeling (SEM) which is operated through the SmartPLS program. The results showed that social support had a positive and significant effect on Person-environment fit through the mediation of Affective Commitment. This shows that Affective Commitment mediates social support for Person-environment fit on the object of research.